4(2x-3)+4x=-2(4x+1)-20

Simple and best practice solution for 4(2x-3)+4x=-2(4x+1)-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-3)+4x=-2(4x+1)-20 equation:


Simplifying
4(2x + -3) + 4x = -2(4x + 1) + -20

Reorder the terms:
4(-3 + 2x) + 4x = -2(4x + 1) + -20
(-3 * 4 + 2x * 4) + 4x = -2(4x + 1) + -20
(-12 + 8x) + 4x = -2(4x + 1) + -20

Combine like terms: 8x + 4x = 12x
-12 + 12x = -2(4x + 1) + -20

Reorder the terms:
-12 + 12x = -2(1 + 4x) + -20
-12 + 12x = (1 * -2 + 4x * -2) + -20
-12 + 12x = (-2 + -8x) + -20

Reorder the terms:
-12 + 12x = -2 + -20 + -8x

Combine like terms: -2 + -20 = -22
-12 + 12x = -22 + -8x

Solving
-12 + 12x = -22 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-12 + 12x + 8x = -22 + -8x + 8x

Combine like terms: 12x + 8x = 20x
-12 + 20x = -22 + -8x + 8x

Combine like terms: -8x + 8x = 0
-12 + 20x = -22 + 0
-12 + 20x = -22

Add '12' to each side of the equation.
-12 + 12 + 20x = -22 + 12

Combine like terms: -12 + 12 = 0
0 + 20x = -22 + 12
20x = -22 + 12

Combine like terms: -22 + 12 = -10
20x = -10

Divide each side by '20'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 4(3x-2)=4x+10+3x-1x | | -6*-11= | | 5x+3500-6.6x=0 | | 1/8-5/12 | | 2x+2X+6= | | -5w+3=(1-2w) | | 12-5p=7 | | x^2-12+56=0 | | .50x-3=1 | | 6x+2=31232 | | 8x-5-5x+4=29 | | .5x-3=1 | | 5r-2=3r+14 | | -1-2lnx=0 | | 4x-8+2x+6=6 | | 6-4(3p-2)=2(p+5) | | 3(7+3x)+1=85 | | -180/y=15 | | 3(2n+5)=7(6n+4)+9 | | 0.3x-0.5x-17=1 | | 11*1/3x=-1 | | 2(x-6)=-3x+8 | | 1/3(12.56h)=25.12 | | 2(x-6)=-3x+3 | | 0.06(y-1)+0.20y=0.10y-0.9 | | 5ln(3z)=14 | | 3.5y=4.5y-y | | 2x-x+3=10-3 | | 32/x=25/9 | | 9(x-1)-1=3x+6(-1+x) | | 39-4x=9-10x | | log4x=1/2 |

Equations solver categories